A breakthrough Trichosporon asahii infection in an immune thrombocytopenia patient during caspofungin and isavuconazole combined therapy: a case report - Lu, Yan; Sun, Yanting; Li, Yankun; Wang, Yingjie; Wu, Dawei; Li, Zhi; Guo, Xi (Frontiers in Cellular and Infection Microbiology, 2025)
Trichosporon infection is a rare but highly lethal infectious disease. Clinically, Trichosporon asahii is the strain most commonly isolated from patients with Trichosporon infections. T. asahii is an opportunistic pathogen that can cause local or invasive infections in immunocompromised patients. In this article, a case of breakthrough T. asahii infection in an immune thrombocytopenia (ITP) patient during caspofungin and isavuconazole combined therapy is reported. Metagenomic next-generation sequencing (mNGS) played a crucial role in the diagnosis of the breakthrough infection in this patient. Upon receiving combined therapy with intravenous voriconazole and nebulized amphotericin B, the patient demonstrated significant clinical improvement and was subsequently discharged.